Shared Mobility: A Reflection on Sharing Economy Initiatives in European Transportation Sectors - Lukasiewicz, Agnieszka (2022)
Freedom of movement is a fundamental human right. The transportation sector, therefore, holds high socio-economic significance—while contributing almost a quarter of Europe’s greenhouse gas emissions and being a major air polluter. Key parts of the ‘collaborative and sharing economy’ relate to transport, including peer-to-peer and on-demand transportation. While these forms of ‘collaborative consumption’ may be seen as promoting environmental sustainability, such models also generate inequality and regulatory disputes (e.g., Uber’s workers and licences), leading to stakeholder conflict. This chapter examines the importance of the main shared mobility services within the transportation sector, their contribution to changing mobility habits, and their connection to sustainable development issues. We also consider conflicts in different European countries caused by shared mobility and the possible effects of the COVID-19 pandemic.